Influence of Heat Treatment on the Anelastic Properties of MgB(2) - da Silva, Marcos Ribeiro [UNESP]; Grandini, Carlos Roberto [UNESP] (Trans Tech Publications Ltd, 2010)
The discovery of the superconductivity of MgB(2) was of great importance, because this material is one of the few known binary compounds and has one of the highest critical temperatures (39 degrees K). As MgB(2) is a granular compound, it is fundamentally important to understand the mechanisms of the interaction of the defects and the crystalline lattice, in addition to the eventual processes involving the grain boundaries that compose the material. In this sense, the mechanical spectroscopy measurements constitute a powerful tool for this study, because through them we can obtain important information about phase transitions, the behavior of interstitial or substitutional elements, dislocations, grain boundaries, diffusion, instabilities, and other imperfections of the lattice. For this paper, the samples were prepared using the PIT method and were characterized by density, X-ray diffraction, scanning electron microscopy, electric resistivity, magnetization, and mechanical spectroscopy. The samples were measured in their as-cast condition and after an ultra-high-vacuum heat treatment. The results showed complex spectra, in which were identified relaxation processes due to dislocation movement, interaction among interstitial elements and dislocations, auto-diffusion, and movement of grain boundaries. Some of these processes disappeared with the heat treatment.
Keywords: MgB(2); Anelasticity; Heat Treatments; Superconductivity